2011
DOI: 10.1016/j.ydbio.2011.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the C. elegans molt by pqn-47

Abstract: C. elegans molts at the end of each of its four larval stages but this cycle ceases at the reproductive adult stage. We have identified a regulator of molting, pqn-47. Null mutations in pqn-47 cause a developmental arrest at the first larval molt, showing that this gene activity is required to transit the molt. Mutants with weak alleles of pqn-47 complete the larval molts but fail to exit the molting cycle at the adult stage. These phenotypes suggest that pqn-47 executes key aspects of the molting program incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 64 publications
1
52
0
Order By: Relevance
“…Next, using linkage analyses, we mapped ju1121 to myrf-1 (F59B10.1, previously named pqn-47 ) (Russel et al, 2011) and determined that ju1121 is a G-to-T change at nucleotide 821 of the myrf-1 open reading frame (Figure 1C). MYRF-1 is a C. elegans ortholog of the recently identified Myrf (myelin regulatory factor) family (Emery et al, 2009; Li and Richardson, 2016; Senoo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, using linkage analyses, we mapped ju1121 to myrf-1 (F59B10.1, previously named pqn-47 ) (Russel et al, 2011) and determined that ju1121 is a G-to-T change at nucleotide 821 of the myrf-1 open reading frame (Figure 1C). MYRF-1 is a C. elegans ortholog of the recently identified Myrf (myelin regulatory factor) family (Emery et al, 2009; Li and Richardson, 2016; Senoo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that myrf-1 is widely expressed in many tissues, including neuronal, muscle, and epidermal seam cells (Russel et al, 2011). However, these initial analyses did not determine myrf-1 expression within specific neuronal subsets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier study in C. elegans found that Myrf-1 was predominantly endoplasmic reticulum (ER) localized (Russel et al, 2011). Intriguingly, mammalian studies showed that MYRF proteins undergo autocleavage in the ER membrane to separate a C-terminal transmembrane domain from an N-terminal DNA binding domain that translocates into the nucleus following cleavage (Bujalka et al, 2013;Li et al, 2013).…”
mentioning
confidence: 99%